Pengaruh Perputaran Piutang Terhadap Return on Assets (ROA) pada PT. Summarecon Agung, Tbk. - Muhibah Muhibah; Tri Septiawan Yunus (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
The purpose of this study to determine the effect of receivable turnover on Return On Assets (ROA) at PT Summarecon Agung Tbk. the period 2014-2019. This research uses qualitative data and quantitative data. The data source used is secondary data. The analysis method used is simple regression analysis, the correlation coefficient (r) and the coefficient of determination (r2). The results showed that receivable turnover has a positive and significant effect on return on assets (ROA) at PT. Summarecon Agung, Tbk. Based on the results of the coefficient of determination of 0.946, it means that the return on assets (ROA) is influenced by receivable turnover of 94.6% and the remaining 5.4% is influenced by other factors not examined. The hypothesis in this study is accepted.